Optimizing Bandung City Space: Improving Environmental Cleanliness and Controlling Street Vendors - Gultom, Wida Bonor; Ivanna, Julia (CV. Rayyan Dwi Bharata, 2024)
Street vendors (PKL) are a profession that is impossible to eliminate from public open space activities, especially in commercial trade areas. The rise of street vendors is now no longer in accordance with city planning. However, on the other hand, they are not only a complement but also a theatrical element of life. city public. With this incident, the Bandung City Government created a policy to regulate these street vendors by establishing a Bandung City Regional Regulation Number 4 of 2011 concerning the Arrangement and Development of Street Vendors. The problem studied in this research is whether the policy model for structuring street vendors in the city has a big impact on optimizing Bandung city space and whether the peddler arrangement pattern is in accordance with the public area layout so that it is hoped that it can become a model for peddler regulation in the city of Bandung.